INVESTIGATING THE EFFECT OF BALANCED SCORECARD ACCEPTANCE ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEM AND SUSTAINABLE PERFORMANCE (COMPANIES LISTED ON THE IRAQI STOCK EXCHANGE) (World Bulletin of Management and Law, 2022)
The purpose of this study was to investigate the effect of accepting a balanced scorecard on the effectiveness of the accounting information system and the sustainable performance of companies listed on the Iraqi Stock Exchange. Descriptive-correlation method was used to conduct this research. The statistical population of the present study included 325 accountants and internal auditors and financial managers of companies listed on the Iraqi Stock Exchange, which according to the Cochran's formula, a total sample size of 176 people was determined. Field method and questionnaire to examine the research variables, a questionnaire tool with 48 questions was used. The reliability of the questionnaires was confirmed by Cronbach's alpha coefficient, the content validity of the questionnaires was confirmed by a group of university professors and their construct validity was confirmed by confirmatory factor analysis. Parametric inferential statistical methods, such as Kolmogorov-Smirnov test, were used to ensure the normality of the variables and structural equation modeling and path analysis using LISREL software to test the hypotheses. The most important research findings showed that Acceptance of Balanced Scorecard had a positive and significant effect on the effectiveness components of the accounting information system and the effectiveness components of the accounting information system also had a positive and significant effect on sustainable performance